Highly Enantioselective Catalytic Dynamic Resolution of N-Boc-2-lithiopiperidine: Synthesis of (R)-(+)-N-Boc-Pipecolic Acid, (S)-(−)-Coniine, (S)-(+)-Pelletierine, (+)-β-Conhydrine, (S)-(−)-Ropivacaine, and Formal Synthesis of (−)-Lasubine II and (+)-Cermizine C - Beng, Timothy K. (2010)
[Image: see text] The catalytic dynamic resolution (CDR) of rac-2-lithio-N-Boc-piperidine using chiral ligand 8 or its diastereomer 9, in the presence of TMEDA has led to the highly enantioselective syntheses of either enantiomer of 2-substituted piperidines using a wide range of electrophiles. The CDR has been applied to the synthesis of R- or S-pipecolic acid derivatives, (+)-β-conhydrine, (S)-(+)-pelletierine, (S)-(−)-ropivacaine, and formal synthesis of (−)-lasubine II and (+)-cermizine C.